Effectivity of Mangkokan Leaf Extract (Nothopanax scutellarium Merr) with Different Treatments to Control Golden Snail (Pomacea canaliculata Lamarck) - Rusdi Rusli; Imelda Sari; Munzir Busniah (Jurnal Proteksi Tanaman, 2022)
Mangkokan leaves (Nothopanax scutellarium Merr) have been used to control golden snail (Pomacea canaliculata Lamarck) in several preparations. This research aimed to study the most effective preparation of the mangkokan leaf extract to control the golden snail. The research was conducted in the Insect Bioecology Laboratory and agriculture field in Batu Busuak Village, Pauh District, Padang City, from March to April 2021. This study used a Completely Randomized Design (CRD) consisting of five treatments and five replications. The treatments were several preparations of mangkokan leaves with a concentration of 5 g/l: control, fresh, boiled, sun-dried, and oven-dried. The observed variables were mortality of the golden snail, the weight of feed consumed, and the decrease in the eating activity of the golden snail. The result showed that botanical molluscicide from mangkokan leaves preparation by oven-dried and fresh were the two most effective in controlling the golden snail because they caused 100 % mortality of the golden snail, reduced the feed number consumed, with decreasing in feeding activity of 54.91% and 52.94%.